General Route to Colloidal Nanocrystal Clusters with Precise Hierarchical Control via Star-like Nanoreactors - Kong, Huimin (Langmuir : the ACS journal of surfaces and colloids, 2021)
A colloidal nanocrystal cluster (CNC) is a hierarchical nanostructure formed by clustering several nanocrystals into one nano-ensemble, which may exhibit unique optical or catalytic properties different from individual nanocrystals owing to the mutual interactions among neighboring component nanocrystals. However, there is still no universal synthetic route that could be applicable to diverse material compositions with precisely controlled hierarchical structures (i.e., nanocrystal number density, component nanocrystal size, and overall diameter of the CNC) up to now. Herein, a general and novel synthetic strategy was reported for crafting a wide range of inorganic CNCs (i.e., noble metal, semiconductor, and metal oxide) via utilizing amphiphilic star-like poly(4-vinylpyridine)-block-polystyrene diblock copolymers as nanoreactors prepared by sequential atom transfer radical polymerization. The hierarchical structure of rationally designed CNCs could be readily tailored by varying the P4VP molecular weight of star-like nanoreactors and the parameter optimization during the CNC preparation process, which was inaccessible by conventional synthetic methods